Making and breaking the Yugoslav working class : the story of two self-managed factories - Musić, Goran, 1981- (Work and labor : transdisciplinary studies for the 21st century, 2021)
"Workers' self-management was one of the unique features of communist Yugoslavia. It prevailed, though not without challenges. Goran Musić has investigated the changing ways in which blue-collar workers perceived the recurring crises of the regime. Two self-managed metal enterprises-one in Serbia, another in Slovenia-provide the framework of the analysis between 1945 and 1989. These two factories became famous for strikes in 1988 that evoked echoes in popular discourses in former Yugoslavia. Drawing on interviews, factory publications and other media, local archives, and secondary literature, Musić analyzes the two cases, going beyond the cliches of political manipulation from the top and workers' intrinsic attraction to nationalism. The author explains how, in the later phase of communist Yugoslavia, growing social inequalities among the workers and undemocratic practices inside the self-managed enterprises facilitated the spread of a nationalist and pro-market ideology on the shop floors. Restoring the voice of the working class in history, Musić presents Yugoslavia's workers as actors in their own right, rather than as a mass easily manipulated by nationalist or populist politicians. The book thus seeks to open a debate on the social processes leading up to the dissolution of Yugoslavia"--